ARTIFICIAL INTELLIGENCE: THE NEXT PHASE OF COMPUTERS IN COUNSELLING - Conger, Stuart D. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1986)
Computer assisted client counselling related programs such as psychological test administration and interpretation, and occupational and educational choice systems have increasingly used some modest features typical of some aspects of artificial intelligence. New programs that will make greater use of artificial intelligence in the short term will be expert advisory systems for use in the training and continuing education of counsellors. In the longer term it is probable that experimental programs using natural language programs will be created to freely engage the client in goal directed conversations in limited domains. Both types of projects will require much new research in the counselling process. RÉSUMÉ Les programmes d’orientation gérés par ordinateur tels que les programmes d’administration et d’interprétatin de tests psychologiques et les systèmes de choix professionnels et éducatifs ont de plus en plus recours à des caractéristiques propres à certains aspects de l’intelligence artificielle. L’on peut prédire que les nouveaux programmes qui feront de plus en plus appel à l’intelligence artificielle à court terme seront les systèmes consultatifs dont on se servira dans la formation et l’éducation permanente des conseillers d’orientation. A plus long terme, il est probable que des programmes expérimentaux basés sur les programmes de langage naturel seront créés pour inciter le client a entamer une conversation dirigée dans certains domaines restreints. Les deux types de projets nécessiteront de nouvelles recherches dans le domaine de l’orientation.